2010
DOI: 10.3168/jds.2009-3007
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of ad libitum whole milk prior to weaning and prepubertal protein supplementation on skeletal growth rate and first-lactation milk production

Abstract: Our objectives were to determine the effects of rapid growth rate during the preweaning period and prepubertal protein supplementation on long-term growth pattern and milk production during the first lactation. Forty-six Israeli Holstein heifer calves were fed either milk replacer (MR) or whole milk (WM) from 4 to 60 d age. Calves had free access to WM or MR for 30 min twice daily and free-choice water and starter mix for the entire day. From weaning until 150 d of age, all heifers were fed the same ration. At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
115
2
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(141 citation statements)
references
References 33 publications
18
115
2
6
Order By: Relevance
“…Utilization of high energy diet has been shown to reduce the mammary parenchymal growth in replacement heifers [23] and ewe lambs [24,25] and is in agreement with current results, while milk protein concentration did not differ. In this reason, the HQD probably had high energy and increased mammary fat pad during the preweaning period (mammary allometric growth phase) and depressed mammary tissue secretion [25].…”
Section: Milksupporting
confidence: 82%
“…Utilization of high energy diet has been shown to reduce the mammary parenchymal growth in replacement heifers [23] and ewe lambs [24,25] and is in agreement with current results, while milk protein concentration did not differ. In this reason, the HQD probably had high energy and increased mammary fat pad during the preweaning period (mammary allometric growth phase) and depressed mammary tissue secretion [25].…”
Section: Milksupporting
confidence: 82%
“…Similarly, Svensson and Hultgren (2008) found that both a higher AFC and higher daily weight gains from weaning to first service were associated with higher milk production in Swedish cattle while Carson et al (2000) found that high growth rates of up to 0.95 kg/day from 3 to 10 months had no detrimental effect on yields. The benefits of better early feeding could, however, be undone by inadequate protein intakes post-weaning (Moallem et al, 2010).…”
Section: Milk Productionmentioning
confidence: 99%
“…Calves provided with higher volumes of milk in early life can consume 20% of their BW daily and gain weight by up to 1 kg/day (Khan et al, 2011). Calves will choose to drink about 8 l/day whole milk in the 1 st month of life (Appleby et al, 2001;Jasper and Weary, 2002;Moallem et al, 2010). This is equivalent to the metabolisable energy (ME) from about 1.1 kg/day of a typical milk replacer (22% protein, 18% fat, 7% ash, therefore ME = 19.7 megajoules/kg dry matter (DM)).…”
mentioning
confidence: 99%